2020
DOI: 10.1111/eip.13052
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COVID‐19 pandemic on youth mental health among youth with physical health challenges

Abstract: Aim To examine mental health in conjunction with physical health during the COVID‐19 pandemic among youth with physical health conditions compared to those without. Methods A cross‐sectional survey of 622 youth aged 14 to 28 was conducted. Analyses were conducted to understand the changes in mental and physical health among youth in four groups: (a) participants with a friend or family member diagnosed with COVID‐19, (b) participants with symptoms associated with COVID‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 42 publications
(45 reference statements)
7
37
0
Order By: Relevance
“…Canadian research on COVID-19 and its impact on mental health and other outcomes is only now starting to be released. For example, Hawke et al (2020) examined mental health among youth with and without physical health challenges during the early stages of COVID-19. Participants in their sample of 14 to 28 year-olds indicated that youth with pre-existing physical health conditions (e.g., asthma, diabetes) and those with symptoms associated with COVID-19 (i.e., fever, shortness of breath, cough/sore throat) reported more impact on their mental health and physical health than those without pre-existing mental and/or physical health concerns.…”
Section: Adolescents and Covid-19mentioning
confidence: 99%
“…Canadian research on COVID-19 and its impact on mental health and other outcomes is only now starting to be released. For example, Hawke et al (2020) examined mental health among youth with and without physical health challenges during the early stages of COVID-19. Participants in their sample of 14 to 28 year-olds indicated that youth with pre-existing physical health conditions (e.g., asthma, diabetes) and those with symptoms associated with COVID-19 (i.e., fever, shortness of breath, cough/sore throat) reported more impact on their mental health and physical health than those without pre-existing mental and/or physical health concerns.…”
Section: Adolescents and Covid-19mentioning
confidence: 99%
“…For example, educational progress and experiences, employment, and social interaction have been disrupted, which may constitute risk factors for emerging or worsening MHSU challenges. Indeed, youth are experiencing mental health challenges during the pandemic [7][8][9][10][11][12] , including heighted symptoms of internalizing mental health challenges 7,13 , post-traumatic stress disorder 10,13 , and general stress and distress [10][11][12] . Behaviors associated with the maintenance of positive mental and physical health, such as physical activity and sleep, have also been disrupted for many youth 12,14,15 .…”
mentioning
confidence: 99%
“…Research from the early period of the COVID-19 pandemic indicates children and young people with pre-existing physical and mental health conditions may be particularly impacted by the pandemic. Mental health concerns appeared to be exacerbated in a sample of young people with pre-existing physical health concerns, particularly those with allergies or asthma (Hawke et al, 2020). Young people with a pre-existing mental illness have also reported significant levels of depression, anxiety and PTSD in the US .…”
Section: Introductionmentioning
confidence: 94%